2016 IEEE 16th International Conference on Advanced Learning Technologies (ICALT) 2016
DOI: 10.1109/icalt.2016.48
|View full text |Cite
|
Sign up to set email alerts
|

Dutch Cooking with xAPI Recipes: The Good, the Bad, and the Consistent

Abstract: Abstract-This short paper presents the experiences of several Dutch projects in their application of the xAPI standard and different design patterns including the deployment of Learning Record Stores. In this paper we share insights and argue for the formation of an international Special Interest Group on interoperability issues to contribute to the Open Analytics Framework as envisioned by SoLAR and enacted by the Apereo Learning Analytics Initiative. Therefore, we provide an overview of the advantages and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The solution discussed in section 3.6 consisted in using the Linear Mixed Effect Models as they allow (1) taking into account data specific to each learner; (2) distinguishing between fixed and random effects; (3) taking categorical data into account. Despite LMEM being the appropriate model for the intended task, the R-squared evaluation test yielded poor prediction accuracies for the five outputs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution discussed in section 3.6 consisted in using the Linear Mixed Effect Models as they allow (1) taking into account data specific to each learner; (2) distinguishing between fixed and random effects; (3) taking categorical data into account. Despite LMEM being the appropriate model for the intended task, the R-squared evaluation test yielded poor prediction accuracies for the five outputs.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of using xAPI is interoperability: learning data from any system or resource can be captured and eventually queried by the third party authenticated services. For each event captured in Learning Pulse, an xAPI statement template was designed following the Dutch xAPI specification for learning activities [2] 5 .…”
Section: Experience Apimentioning
confidence: 99%
“…Standards for data models and data collection in e-learning are still lacking [6], [7] and pose a barrier to the scaling and interoperability of LA. Our proposed pipeline is optimized to work with LA data conforming to the Experience API (xAPI) standard [8] in the JSON format, but is also adaptable to work with LA specifications and formats from other platforms.…”
Section: A Data Formats and Interoperabilitymentioning
confidence: 99%
“…Provided consent has been given, the platform's learning spaces and the applications within them capture LA data conforming to the Experience API (xAPI) [8] standard. Predefined user interactions with a learning space or application, such as navigation between lessons or the typing of text into an input box, generate data points known as actions, which are sent to and stored on the platform's servers.…”
Section: Data Gatheringmentioning
confidence: 99%
“…Their results also showed that students had different operating habits and learning paths which provided the basis for the evaluation of students' spatial thinking ability and engineering design skill in the interactive learning environment. The authors in [108] discussed some experiences and learnt lessons from implementing xAPI for projects in the Netherlands. The authors remarked on the need for a centralized approach for data collection to get a complete picture of student behavior which may be stored on many heterogeneous IT systems.…”
Section: ) Learning and Assessment Analytics Using Experience Apimentioning
confidence: 99%